TINDAK TUTUR ILOKUSI DIREKTIF PADA PODCAST WARUNG KOPI (PWK) DALAM EDISI DAVINA KARAMOY DI HAS CREATIVE - Anisa Zikriyah Oktaviana; Eko Suroso; Sukirno; Eko Muharudin (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study aims to identify and describe the forms of directive illocutionary discourse acts in the podcast Warung Kopi bersama Davina Karamoy, which airs on the HAS Creative channel. This study employs a qualitative descriptive approach, with data consisting of utterances containing directive elements, sourced from podcast videos uploaded in May 2025. Data collection was conducted using the Simak Bebas Libat Cakap (SBLC) method. Data analysis followed the Miles and Huberman model, consisting of three stages: data reduction, data presentation, and drawing conclusions. The results of the study indicate the presence of various forms of directive illocutionary discourse acts, such as questions, commands, prohibitions, and advice, which are used to direct, request, and influence the actions of the interlocutor. Among these forms, questions and commands are the most dominant, consistent with the interactive and spontaneous nature of podcasts. Thus, this study confirms that directive illocutionary acts play a significant role in establishing communicative interaction, particularly in the context of digital media.